Strategy of Batam City Governance in Implementing the Free Halal Certification Program: Governance Perspective - Nur Ambia Arma; Faizal Madya (Journal Public Policy, 2026)
The Halal Certification Program (SEHATI) is a strategic policy aimed at enhancing the competitiveness of MSMEs. The Batam City Government has set a target of 8,000 certifications by 2024 as a form of support for this national policy. This study aims to evaluate the program’s implementation through a meta-governance perspective to provide critical insights for stakeholders. Using a mixed-methods approach with a parallel convergent design, data were collected through focus group discussions, in-depth interviews, document reviews, and a satisfaction survey of 100 micro-business owners. The analysis was conducted by integrating the SWOT/TOWS matrix to create strategic priorities. The findings reveal a governance paradox: the program has successfully gained strong social legitimacy based on service performance (output legitimacy), yet remains structurally fragile due to institutional fragmentation, the absence of a formal legal framework at the local level, and weak inter-agency data integration. This study concludes that the sustainability of SEHATI in Batam requires a transformation from an operational facilitation function toward the strengthening of an institutionalized meta-governance structure. Key recommendations include the codification of local regulations, the establishment of a regional Halal Certification Body (LPH), and cross-sectoral data synchronization to mitigate structural barriers and the threat of illegal products.